Prevalence and Risk Factors for Severe Acute Malnutrition among Less Than Five Children from an Urban Locality of Surat City, Western India - Varsha Gupta; Aseem Garg; Harsimranjit Kaur Natt; Rikita Munshi (Medsci Publications, 2022)
Introduction Undernutrition puts children at greater risk of dying from common infections, increases the frequency and severity of such infections, and delays recovery. The percentage of undernutrition, stunting and wasting in children under 5 years of the age in India are 35.7, 38.4 and 21.0 respectively. The etiology of malnutrition is complex and multi-factorial usually a consequence of inadequate dietary intake and various diseases. Methodology: A community based case-control study was conducted among children aged 6 to 59 months, registered at the Anganwadi centers in an urban locality of Surat city, Gujrat. Study population was divided into cases and controls using WHO classification based on anthropometric measurements. Result: The prevalence of undernutrition and severe acute malnutrition among the under-five children were 26.2 and 8.7% respectively. Significant association was found between nutritional status of the children and type of the family(  OR 3.84, 95% CI =1.87-7.86, p = 0.000), low birth weight (OR 4.85, 95% CI =2.29 - 10.26, p = 0.000), poor appetite (OR = 2.89, 95% CI = 1.38-6.01, p = 0.004), bottle feeding (OR = 5.41, 95% CI = 1.91-15.29, p= 0.001) and children with habits of eating wafers/candies (OR = 21.99, 95% CI = 9.02-53.60, p = 0.000). Conclusion: Severe acute malnutrition continues to be an important health concern among under five children in the urban area and is affected by many risk factors which can be mitigated through structured and timely interventions using IEC materials.